2018
DOI: 10.1186/s40634-018-0149-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of knee flexion and extension on the tibial tuberosity–trochlear groove (TT–TG) distance in adolescents

Abstract: BackgroundMeasurement of the tibial tubercle–trochlear groove (TT–TG) distance is used to assess patellofemoral instability and rotation. Since patellofemoral instability and acute patellar dislocation are common among adolescents, it is important to clarify the relationship between TT–TG distance and various flexion and extension angles in asymptomatic children. The purpose of the present study was to determine how knee flexion and extension influence TT–TG-distance values measured using 3D imaging in an anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
1
13
1
4
Order By: Relevance
“…The TT-TG distance values ranged between 5-17 mm in extension, which is considered as being normal [12,13]. Our results showed an overall tendency of decreased TT-TG distance values over knee flexion, which coincides with previous findings [8,7]. The medial/lateral TT position and TT-TG distance showed a good correlation in extension (Figure 2 (B)), which have not been reported previously to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The TT-TG distance values ranged between 5-17 mm in extension, which is considered as being normal [12,13]. Our results showed an overall tendency of decreased TT-TG distance values over knee flexion, which coincides with previous findings [8,7]. The medial/lateral TT position and TT-TG distance showed a good correlation in extension (Figure 2 (B)), which have not been reported previously to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…An established radiographic measure to quantify the relative rotational alignment of the femur and tibia in extension is the tibial tuberosity-trochlear groove (TT-TG) distance. It has been measured recently at different flexion angles under non-weight-bearing conditions [7]. However, Izadpanah et al [8] reported that it also depends on weight-bearing.…”
Section: Introductionmentioning
confidence: 99%
“…PFI is a common disease in orthopedic sports medicine [2], especially in women aged 10-17 years [3][4][5]. The incidence rate is approximately between 7 and 49 people per 100,000 [3,5,6]. If the patellofemoral joint is unstable, every instance of flexion and extension of the knee joint will cause uneven stress and wear of the articular cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, magnetic resonance imaging (MRI) has been gradually used to identify the position of the tibial tuberosity, with the advantages of evaluating soft tissue structures and the articular cartilage with no radiation [16][17][18]. However, the TT-TG distance measured on CT images is still considered as a gold standard [6,[19][20][21]. Several studies have emphasized factors that may have an effect on the value of TT-TG distance, such as trochlear dysplasia and knee rotation [16,22,23].To expel the influence of these variables, Seitlinger et al [19,23,24] have proposed to judge PFI with MRI-the tibial tubercleposterior cruciate ligament (TT-PCL) distance.…”
Section: Introductionmentioning
confidence: 99%
“…While the TT-TG may be better than the TT-PCL for identifying those with patellofemoral instability, it is well known that surgeons must use care when utilizing the TT-TG as numerous variables, including knee flexion angle, tibial rotation, knee size, weight bearing status, and imaging modality, may all affect measurements. [11][12][13][14][15][16][17][18][19][20] While the TT-TG and TT-PCL measurements provide guidance in the coronal plane, sagittal plane correction is also important to consider, as alignment in this plane can cause significant variation in contact pressure between the patella and trochlea. In 1976, Maquet was the first to describe anteriorizing the tibial tubercle to decrease patellofemoral contact pressures; however, there is still no quantitative tool to guide surgeons in the amount to anteriorize.…”
mentioning
confidence: 99%